Poverty and prosperity : tourism in rural China - Liu, Xinru; Xiao, Honggen (Bridging tourism theory and practice ;, 2023)
Poverty and Prosperity: Tourism in Rural China focuses on tourism and rural community development in the light of Confucianism and Taoism. Drawing from ethnographic field research in Southern China, the authors present an evolutionary as well as a horizontal view of tourism and rural community development through an illustrative case. Narratives from villagers involved in (or affected by) tourism development in the case study village are highly embedded in, and culturally informative of, rural community development with Chinese characteristics. A valuable source of reference and an addition to the pro-poor tourism knowledge, this book offers an epistemologically unique and much needed perspective on researching and practicing tourism for poverty alleviation and rural revitalization.